Don't Downsize This! Social Reactions to Mass Dismissals on Twitter - Andrea Bassanini; Eve Caroli; Bruno Chaves Ferreira; Antoine Reberioux (Global Labor Organization (GLO), 2023)
We study social reactions to job destructions on Twitter. We use information on large-scale restructuring events announced in the United Kingdom over the period 2013-2018. We match it with data collected on Twitter regarding the number and sentiments of the tweets posted around the time of the announcement and involving the company name. We show that jobdestruction announcements immediately elicit numerous and strongly negative reactions. These reactions are almost five times larger than the positive reactions to job-creation announcements. We also show that the negative reactions triggered by job-destruction announcements are associated with significant losses in the market value of the downsizing firms. This suggests that the damage to the firms' image triggered by the negative social reactions following job destructions entail a financial cost for firms that adds to the standard adjustment costs of dismissals.
Keywords: J63; L82; M21; M51; 330; job destructions; firm value; social media; sentiment analysis; mass dismissals